2019
DOI: 10.1177/1558866119840466
|View full text |Cite
|
Sign up to set email alerts
|

Retention and Academic Success of First-Year Student-Athletes and Intramural Sports Participants

Abstract: The purpose of this investigation was to compare the relationship of intramural sports and Division III athletic participation to retention and academic success in first-year college students. A first-year student cohort ( n = 568) was grouped into four categories: no participation, student-athlete, intramural participant, and participant in both. There was no statistically significant difference in academic success among the participant groups, F(6, 1084) = .626, p = .710. Both the student-athlete and intramu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 20 publications
1
22
0
Order By: Relevance
“…Research has examined use of recreation facilities, as well as participation in club and intramural sports. Studies have found campus recreation participants have higher grade point averages (GPAs), retention rates, and graduation rates (Belch et al, 2001; Danbert et al, 2014; Huesman Jr et al, 2007, 2009; Leppel, 2005; Mayers et al, 2017; McElveen & Ibele, 2019; Roddy et al, 2017; Vasold et al, 2019a; Vasold et al, 2019b; Zegre et al, 2020). Beyond institutional outcomes, benefits of campus recreation include physical and mental health outcomes (Brock et al, 2015; Forrester, 2014; Zizzi et al, 2004); Forrester (2014) reported nationwide evidence of positive associations between campus recreation and a range of outcomes including student enrollment, retention, academics, employment, health, and wellness.…”
Section: Using a Data-driven Approach To Examine Facility Use Definit...mentioning
confidence: 99%
See 3 more Smart Citations
“…Research has examined use of recreation facilities, as well as participation in club and intramural sports. Studies have found campus recreation participants have higher grade point averages (GPAs), retention rates, and graduation rates (Belch et al, 2001; Danbert et al, 2014; Huesman Jr et al, 2007, 2009; Leppel, 2005; Mayers et al, 2017; McElveen & Ibele, 2019; Roddy et al, 2017; Vasold et al, 2019a; Vasold et al, 2019b; Zegre et al, 2020). Beyond institutional outcomes, benefits of campus recreation include physical and mental health outcomes (Brock et al, 2015; Forrester, 2014; Zizzi et al, 2004); Forrester (2014) reported nationwide evidence of positive associations between campus recreation and a range of outcomes including student enrollment, retention, academics, employment, health, and wellness.…”
Section: Using a Data-driven Approach To Examine Facility Use Definit...mentioning
confidence: 99%
“…Research reveals positive relationships between participation in campus recreation and academic outcomes including GPA, retention, and graduation (Belch et al, 2001; Danbert et al, 2014; Huesman Jr et al, 2007, 2009; Leppel, 2005; McElveen & Ibele, 2019; Roddy et al, 2017; Vasold et al, 2019a; Vasold et al, 2019b). These studies exhibit a range of research designs and measurement approaches, including surveys, analyses of card-swipe data, descriptive statistics, and regression-based approaches.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Intramural sport programming is a common campus recreation service, with ∼11.7% of undergraduate students in Canada participating in some form of intramural sport programming (American College Health Association, 2019). The contribution of intramural programming to quality postsecondary education is well documented (e.g., Forrester et al, 2018;McElveen & Ibele, 2019;Moffit, 2010;Phipps et al, 2015;Sturts & Ross, 2013). Notably, previous research suggests that participation in intramurals contributes to improved health and physical fitness, greater self-confidence, and improved stress management among students (e.g., Artinger et al, 2006;Forrester, 2015;Huesman et al, 2009).…”
Section: Introductionmentioning
confidence: 99%